Traditional Law Existence in Indonesia in Review From Age To Age - Angelika S, Michelle; Firmansyah, Yohanes; Wijaya, Hanna (Cerdika: Jurnal Ilmiah Indonesia, 2021)
The rules of action are a reflection of the life characteristics of a class of people. Regulations that are timeless and firmly integrated with the citizens' behavior can increase their binding power. As a result, they become customs. In a tradition, there are various rules of the tongue, listed as customary law. Routine or habit is a term commonly used in people's lives. The existence of customary law has been legally recognized by the Indonesian authorities, approved by all Indonesian citizens as one of the legal rules. The citizens can lawfully use it on the side of the authorities' use of laws and regulations. Customary law reflects something Indonesian personality as if the result has been claimed to be like original Indonesian law. As if the law is not recorded, currently, the presence of customary law is being questioned. It has been estimated as conventional, outlandish, ancient primitive, ancient compared to the citizens' modern progress. Some people think that customary law is incapable of solving cases during a period.